“If There Were an Eye on the Back of the Heaven…” (Plotinus, Ennead 4.5,3 and 8) - Cornea, Andrei (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2007)
Our paper discusses two curious passages of Plotinus’ treatise On some difficulties concerning the Soul III. On vision (Enn. 4.5,3 and 8), where the philosopher seems to contemplate the possibility of another universe outside this one. Yet we could never know this other universe, nor could we even decide whether it exists or not, even if “there were an eye on the back of the Heaven” able to look at it at close range. In fact, Plotinus explains, different universes cannot communicate at all among themselves. If they could, they would no longer be separate universes, but only parts of the same universe, because communication (or in Plotinian terms, sympathy) flows only within the same universe. We compare this interesting argument to some modern astrophysical ideas, as well as to the “philosophy of possible worlds” of David Lewis, while trying to avoid any “modernizing” perspective on Plotinus.